Can someone explain me please why

$2 \vec U \vec V cos(\omega t + \phi _1)cos(\omega t + \phi _2) = U V cos(\alpha )cos(2\omega t + \phi _1+\phi _2)+(cos\phi _1 - \phi _2) $,

where $\alpha$ is the angle between the vectors $\vec U$ and $\vec V$.

I just don't see it, It's from my physics book and I don't understand this step. I tried to use $cos(a+b) = cos(a)cos(b) - sin(a)sin(b)$ but I think it's nonsense because of that $sin$ and I didn't find any trigonometry identity which would help me neither.


The identity does not hold true as posted, for example if $\omega = t = \phi_1 = \phi_2 = 0$ it reduces to $2 \vec U \vec V = UV \cos (\alpha)$ instead of the correct $2 \vec U \vec V = \color{red}{2}UV \cos (\alpha)\,$.

What does hold true, however, is: $$2 \vec U \vec V \cos(\omega t + \phi _1)\cos(\omega t + \phi _2) = U V \cos(\alpha )\big(\cos(2\omega t + \phi _1+\phi _2) \color{red}{+}\cos(\phi _1 - \phi _2)\big) $$

The above follows from the trigonometric identity $\cos(a+b)+\cos(a-b)=2 \cos(a)\cos(b)$.

  • $\begingroup$ I have made a mistake, i will edit it and thank you very much! I have spent ages on this. $\endgroup$ – Leif Sep 11 '17 at 0:52

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.